Pengaruh Promosi Iklan Medsos Terhadap Kesadaran Merek pada Jasa Usaha Cuci Sepatu - Farhan Abdillah; Arwanda Siddik; Sarwoto Sarwoto; Willy Cahyadi (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to determine the effect of social media advertising promotions on brand awareness. The research method used is a quantitative method. The population in this study is Kang Cuci Patu's Instagram followers. Determination of the number of samples using the Slovin formula with a 10% error rate. Data were collected by distributing questionnaires using a Likert scale with a sample of 97 respondents. The data analysis methods applied include validity tests, reliability tests, classical assumption tests, simple linear regression analysis, coefficient of determination (R²) tests, and partial tests (t-tests) using IBM SPSS Statistics 25. The research findings indicate that advertising through social media has a positive and significant impact on brand awareness. The results of the t-test show a t-count value of 17.537 which is greater than the t-table of 1.98 and a significance level of 0.000 <0.05. The results of a simple linear regression analysis yield the following formula: Y = 0.984 + 0.934 X + e. The coefficient of determination (R²) of 0.764 indicates that promotion through social media advertising can explain 76.4% of the influence on brand awareness, while the remainder is influenced by other factors not examined. This research has a novelty in the object of study, namely the Kang Cuci Patu shoe washing service in Tebing Tinggi City, which has not been widely researched in digital marketing literature. This study provides an empirical contribution regarding the effectiveness of social media advertising promotions in creating brand awareness which is relatively rarely researched, especially in non-metropolitan areas. This study shows that promotion through social media platforms such as Instagram and TikTok is successful in increasing brand awareness of shoe cleaning services in Tebing Tinggi City.